2005
DOI: 10.1176/appi.psy.46.5.385
|View full text |Cite
|
Sign up to set email alerts
|

The Occupational and Psychosocial Impact of SARS on Academic Physicians in Three Affected Hospitals

Abstract: A cross-sectional anonymous survey was administered to all directory-listed physicians within a network of three large teaching hospitals that provided care to SARS patients in Toronto. One hundred ninety-three physicians participated, 23% of whom provided direct care to SARS patients. A significantly higher rate of psychological distress was seen among physicians providing direct care to SARS patients (45.7%) than among those not providing direct care (17.7%), and physicians providing direct care reported fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(187 citation statements)
references
References 19 publications
12
169
0
3
Order By: Relevance
“…20 Although one study reported that being deployed to work in other work units with new colleagues as being a factor that would increase the perception of risk, 20 other studies indicated that there was a greater sense of collegiality and togetherness with other HCWs during the SARS outbreak. 15,21…”
Section: Social Isolationmentioning
confidence: 99%
“…20 Although one study reported that being deployed to work in other work units with new colleagues as being a factor that would increase the perception of risk, 20 other studies indicated that there was a greater sense of collegiality and togetherness with other HCWs during the SARS outbreak. 15,21…”
Section: Social Isolationmentioning
confidence: 99%
“…The second unusual characteristic of infectious exposure is that the exposed person is likely to fear not only for his or her own safety but also for the safety of loved ones. Health care professionals, in particular, may be more concerned about infecting family members than they are about becoming infected themselves [13]. Both of these unusual features of exposure to infectious disease reduce the availability of social support, especially support from family, to buffer the impact of stress.…”
Section: Editorialmentioning
confidence: 99%
“…A notable example would be the psychological sequelae observed during the Severe Acute Respiratory Syndrome (SARS) outbreak in 2003(McAlonan et al, 2007Ministry of Health S, 2004). Studies on the SARS outbreak revealed that healthcare workers experienced acute stress reactions (Tam et al, 2004;Grace et al, 2005).…”
Section: Introductionmentioning
confidence: 99%